One‐component, double‐chromophoric thioxanthone photoinitiators for free radical polymerization - Kreutzer, Johannes; Yagci, Yusuf (Wiley, 2017)
ABSTRACTTwo one‐component, double‐chromophoric thioxanthone photoinitiators, namely TX‐EDA and TX‐DETA were synthesized by the reaction of thioxanthone aldehyde (TX‐A) with ethylenediamine (EDA) and diethylenetriamine (DETA), respectively via a facile Schiff base reaction. Both photoinitiators were characterized by spectral analysis and photobleaching studies. DFT calculations are employed to reveal the contribution of the different orbitals to the excitation of the initiators. The double‐chromophoric nature of the initiators gives rise to an increased absorption in the near UV region when compared with the pristine TX‐A. Photoinitiated polymerization of various vinyl monomers with TX‐EDA and TX‐DETA has been investigated in the presence and absence of a co‐initiator and compared for formulations consisting of precursor TX‐A. In addition, real‐time FTIR spectroscopic studies were performed in methyl methacrylate polymerization with both initiators. The higher efficiency observed with TX‐DETA may be attributed to the additional hydrogen donating sites adjacent to nitrogen atoms. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2017, 55, 3475–3482